A tangled triangle of ‘Society – COVID-19 – Information’ - Jana, Sibsankar (Qualitative and Quantitative Methods in Libraries, 2022)
Society’s one of the important attributes is social interaction. However, the recent COVID-19 pandemic disease has drastically affected the norms and communication patterns in our societies. This viral disease has forced us to maintain, stay home stay safe. Moreover, day after day the WHO directs us new information towards combating this deadly virus. As of now, there are no medicines or vaccines for this viral disease. The only thing we can do is ‘Social Distancing’. Therefore, we are getting unsocial. However, being human, we need to communicate with each other to maintain physical distance. Here, information communication via a network is the only means to be social. In this context, various tools and apps play an important role in bridging the gap that evolved during this pandemic situation. The tools comprise social networking, virtual learning, video conferencing, money transferring, movies, songs, etc. This paper depicts the tangled relationship among these three components, namely society, COVID-19, and information in three vertices of a triangle. At the end of the day, the right information can combat the spread of COVID-19 and restore our societal normal activities.